Factors influencing partnerships between care workers and families in nursing homes in South Korea - Eun-Yeong Jung; Hye-Young Jang (Scientific Reports)
Abstract This study aimed to identify factors influencing partnerships between nursing home staff and families and explore means of improving these partnerships. It employed a cross-sectional survey design. Data were collected from 152 care workers who worked in 11 nursing homes in Gyeonggi-do. As research tools, the scale for staff–family partnership in long-term care, global interpersonal communication competence scale, emotional intelligence scale, and organizational culture scale were used. Participants had a mean age of 59.93 ± 7.72 years, and the mean partnership score was 48.81 ± 6.35. Partnership was influenced by communication competence (β = 0.26, p = .002); developmental culture, a sub-domain of organizational culture (β = 0.29, p < .001); and current work experience (β = –0.21, p = .004). The explanatory power was 32.1% (F = 24.81, p < .001, Adj.R² = 0.321). These findings highlight the need for practical strategies to enhance partnerships in nursing homes. Specifically, nurses who manage care workers should foster a work environment that promotes staff retention for more than 3 years through flexible organizational management, provide differentiated, experience-based communication training, and implement supervision to improve care expertise. By applying these measures, nursing homes can strengthen partnerships between staff and families, ultimately improving the quality of care services and the well-being of older residents.